2003
DOI: 10.1046/j.0954-6820.2003.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP‐1 levels in adult women born small for gestational age suggest insulin resistance in spite of normal BMI

Abstract: Abstract. Kistner A, Jacobson SH, Celsi G, Vanpee M, Brismar K (Karolinska Hospital and Karolinska Institutet, Stockholm, Sweden). IGFBP-1 levels in adult women born small for gestational age suggest insulin resistance in spite of normal BMI. J Intern Med 2004; 255: 82-88.Objective. Impaired fetal development may contribute to decreased insulin sensitivity. This study was designed to characterize serum markers of insulin resistance in adults born small for date or born prematurely. Study design. Fifty subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
1
16
4
Order By: Relevance
“…As IGFBP-1 is a marker of insulin sensitivity, 55 this suggests a potentially reduced future risk of CVD. In a Swedish study, adult women born small for gestational age were shorter and had lower IGFBP-1 levels compared with full-term controls, suggesting reduced growth together with relative insulin resistance 56 . In our studied children, however, lower IGF-1 and stunted growth were accompanied by higher IGFBP-1.…”
Section: Discussioncontrasting
confidence: 45%
“…As IGFBP-1 is a marker of insulin sensitivity, 55 this suggests a potentially reduced future risk of CVD. In a Swedish study, adult women born small for gestational age were shorter and had lower IGFBP-1 levels compared with full-term controls, suggesting reduced growth together with relative insulin resistance 56 . In our studied children, however, lower IGF-1 and stunted growth were accompanied by higher IGFBP-1.…”
Section: Discussioncontrasting
confidence: 45%
“…One study associated birth weight positively with IGFBP-1 levels in older age (Kajantie et al 2003), which is in line with our findings. Similarly, in the only other study (Kistner et al 2004) among 50 young adult women, IGFBP-1 levels were lower in adult women born full-term but small for gestational age -yet, a correlation with birth weight was not reported.…”
Section: Discussionmentioning
confidence: 98%
“…Kamoda T et al reported that the levels of serum IGFBP-1 were similar in short children born SGA and AGA [35]. Kistner A et al investigated the serum markers of insulin resistance in adults born SGA and reported that lower IGFBP-1 and triglyceride levels were observed in the SGA group compared to the AGA group despite with normal BMI [36]. In our study, there were no marked differences in IGFBP-1 and triglyceride levels between SGA children with height and BMI catch-up growth and their age-matched controls.…”
Section: Discussionmentioning
confidence: 99%